Performance and innovation in the public sector managing for results - Berman, Evan M.; Hijal-Moghrabi, Imane (Routledge, 2023)
Managing for results is increasingly important for the success of public organizations. Performance and Innovation in the Public Sector is a comprehensive textbook that examines a broad range of performance strategies.
1. Auflage published by Sharpe 1998 u.d.T. Productivity in public and nonprofit organizations
Keywords: Electronic books